Drugs in Ophthalmology - Fong, Donald S.; Law, Simon K.; Schmidt-Erfurth, Ursula M. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
This drug handbook is divided into two sections: Alphabetical Listing of Drugs Entries in this section are listed by generic name. Information for each drug is arranged in a consistent format for easy reference. If one or more of the following categories is not applicable to a certain drug, it will not be listed. If Pregnancy Category is not listed for an individual drug, then it is either listed under the first drug in a group of drugs, or safety and efficacy in pregnancy have not been established. Summary of Anti-infectives This section summarizes the common doses of antibiotics, antifungals, and antivirals. For each drug, the dose for each route of administration is included. Generic name Brand names Common trade names Class of drug Therapeutic class Indications Common uses of the drug Dosage form Common forms of the drug Dose The amount of drug to be given or taken during therapy.